Editorial Notes Vol.11 - Khattri, Man Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2017)
We are happy to present Volume 11 to our dear readers. Many people have contributed in many different aspects in editorial processes. Besides International Advisory Board members we are able to nominate five editors from different institutions and individuals. Their valuable presence in our journal certainly helps building trust, wider visibility and commitment for quality editing and publication. We are delighted with the work of wonderful reviewers, who supported and encouraged us to work further. Without their rigorous work we would not be able to bring this journal in this form. We would like to express our heartfelt thanks and sincere gratitude to all valuable reviewers: Prem Bhandari, Om Gurung, Ram Bahadur Chhetri, Chudamani Basnet, Rajendra Raj Timilsina, Janak Rai, Yogendra Bahadur Gurung, Youba Raj Luitel, Madhu Giri, Chitra Bahadur Budathoki, Madhusudan Subedi, Man Bahadur Khattri, Bishow Bandhu Adhikari, Prakash Prasad Sapkota, Rishikesh Pandey, Binod Pokhrel, Jagan Nath Adhikari, Anita Sherestha, and Mina Uprety. Similarly, we would like to express sincere thanks to Netralal Neupane, Janak Paudel, Tilak Prasad Kandel, Prakash Sharma, Kamal Sharma for their time and hard effort for proof reading.